Rancang Bangun Pengupas Kelapa Muda Berbasis Progam Logic Controller and Human Marchine Interface - Fathul Hadi, Charis; Muliyono, Muliyono (Jurnal FORTECH, 2021)
In general, the design of the young coconut peeler machine is to use an induction motor that still uses a manual system to turn the tool on and off, so it is not efficient in the production process of peeling young coconut. The speed of the induction motor can be adjusted by changing the frequency, therefore a Variable Speed ​​Drive (VSD) is needed which aims to regulate the rotational speed of the induction motor. As the controller of the Variable Speed ​​Drive (VSD), the compiler uses a Programmable Logic Controller (PLC). From the description of the background above, a young coconut peeler based on PLC and HMI was designed. This system uses PLC control as a control for variations in the rotation speed of the motor, so that the rotation of the induction motor can be controlled as needed, in this tool an HMI system is applied which functions as an interface display from the operator to the peeler. In this study using 4 stages, namely (1) a needs survey, (2) designing (3) prototypes, (4) testing prototypes. In the trial results, the simulation of the coconut peeler design went well by using low, medium, high speed variations using the human marchine interface as the display of the variable speed button, while the PLC as the control machine.)